Designed to Be Green, Economic, and Efficient: A Ketone‐Ester‐Alcohol‐Alkane Blend for Future Spark‐Ignition Engines. Issue 23 (12th November 2021) - Ackermann, Philipp; Braun, Karsten E.; Burkardt, Patrick; Heger, Sebastian; König, Andrea; Morsch, Philipp; Lehrheuer, Bastian; Surger, Maximilian; Völker, Simon; Blank, Lars Mathias; Du, Miaomiao; Heufer, Karl Alexander; et al.
Abstract: Model‐based fuel design can tailor fuels to advanced engine concepts while minimizing environmental impact and production costs. A rationally designed ketone‐ester‐alcohol‐alkane (KEAA) blend for high efficiency spark‐ignition engines was assessed in a multi‐disciplinary manner, from production cost to ignition characteristics, engine performance, ecotoxicity, microbial storage stability, and carbon footprint. The comparison included RON 95 E10, ethanol, and two previously designed fuels. KEAA showed high indicated efficiencies in a single‐cylinder research engine. Ignition delay time measurements confirmed KEAA's high auto‐ignition resistance. KEAA exhibits a moderate toxicity and is not prone to microbial infestation. A well‐to‐wheel analysis showed the potential to lower the carbon footprint by 95 percent compared to RON 95 E10. The findings motivate further investigations on KEAA and demonstrate advancements in model‐based fuel design. Abstract : Renewable fuels : Model‐based fuel design can tailor alternative fuels to advanced internal combustion engine concepts while minimizing production cost and global warming impact. A multi‐disciplinary assessment of KEAA, a rationally designed renewable fuel for high efficiency spark‐ignition engines, is presented. KEAA features promising production cost estimates, high engine efficiency, low environmental impact, and a low carbon footprint.